Computational homogenization of the electro‐chemically coupled multi‐scale transport of Li‐ions in structural battery electrolytes. Issue 1 (25th January 2021) - Tu, Vinh; Larsson, Fredrik; Runesson, Kenneth; Jänicke, Ralf
Abstract: The structural battery electrolyte (SBE) is a crucial component for the structural battery, which is an innovative energy storage device. While the SBE must allow for ion transport, it must also contribute to the structural integrity of the battery. In this contribution, we study the electro‐chemical properties of the SBE using finite element analysis. For the governing equations, we use Ampere's law in terms of a balance equation, and also the mass continuity equation of ions, which in the end results in a fully coupled transient multiphysics problem. Due to the strong heterogeneities in the SBE microstructure, a multi‐scale approach is adopted.